Struktur Komunitas Terumbu Karang di Perairan Teluk Balikpapan, Kalimantan Timur - Niken Financia Gusmawati; Candra Dwi Puspita; Herlina Ika Ratnawati (Pusat Riset Kelautan, 2020)
Coral reefs are ecosystems with high productivity while being very vulnerable to environmental changes. The oil spill incident in Balikpapan Bay in 2018 still caused damage to the coral reef ecosystem in Tanjung Jumlai, Penajam Paser Utara Regency, East Kalimantan due to the use of dispersants in handling oil spills. Research on the condition of coral reefs is carried out to ensure the sustainability of the benefits of ecosystem products and services provided by coral reef ecosystems to communities around Balikpapan Bay. Coral reef research has been carried out at three transect station locations in the Tanjung Jumlai reef area. This research is aimed to determine the distribution, abundance, and structure of coral reef ecosystems in these waters. The study was conducted in October 2019. Data collection was carried out using the Point Intercept Transect (PIT) method. The results showed that the average percentage of coral cover was 55.7% with a good coral cover category. Substrate covering the bottom of the coral reef ecosystem is dominated by Acropora Tubulate and Acropora Branching from the biotic component, and Dead Coral with Algae and Rubble from the abiotic component. Diversity index value (H') in the waters is categorized as low species richness. This research has been identified only 10 genera in the study area where 9 genera are hard coral species. Similarity Index value (E) included in the medium category and dominance index value (D) belong to the medium category which means that there are no species that are very dominant in the observation area. Water quality at station 1 representing all observation stations shows results that the study area are still appropriate for marine biota according to Minister of Environment Decree 51/2004, except for nitrate content. Sediments also show no trace of hydrocarbons.Coral reefs are ecosystems with high productivity while being very vulnerable to environmental changes. The oil spill incident in Balikpapan Bay in 2018 still caused damage to the coral reef ecosystem in Tanjung Jumlai, Penajam Paser Utara Regency, East Kalimantan due to the use of dispersants in handling oil spills. Research on the condition of coral reefs is carried out to ensure the sustainability of the benefits of ecosystem products and services provided by coral reef ecosystems to communities around Balikpapan Bay. Coral reef research has been carried out at three transect station locations in the Tanjung Jumlai reef area. This research is aimed to determine the distribution, abundance, and structure of coral reef ecosystems in these waters. The study was conducted in October 2019. Data collection was carried out using the Point Intercept Transect (PIT) method. The results showed that the average percentage of coral cover was 55.7% with a good coral cover category. Substrate covering the bottom of the coral reef ecosystem is dominated by Acropora Tubulate and Acropora Branching from the biotic component, and Dead Coral with Algae and Rubble from the abiotic component. Diversity index value (H') in the waters is categorized as low species richness. This research has been identified only 10 genera in the study area where 9 genera are hard coral species. Similarity Index value (E) included in the medium category and dominance index value (D) belong to the medium category which means that there are no species that are very dominant in the observation area. Water quality at station 1 representing all observation stations shows results that the study area are still appropriate for marine biota according to Minister of Environment Decree 51/2004, except for nitrate content. Sediments also show no trace of hydrocarbons.